Cistercian chant and its liturgical-musical sources. From Robert of Molesmes to Bernard of Clairvaux (History Journal «Jerónimo Zurita», 2023)
When Bernard of Clairvaux took over the Cistercian Order after the death of his predecessor Stephen Harding in 1134, he was faced with a recently completed rigorist reform of monasticism in the Benedictine tradition. Under his rule, he initiated a second reform, reflected in the oldest liturgical-musical documents of the Order. These documents, most of them palimpsests, have required a long work of interpretation and restitution, which today makes it possible to reveal a forgotten liturgical and musical tradition, the one prior to Bernard and, therefore, that of the first chant that was practiced in the Cistercian order between 1110 and 1143.
Keywords: Cistercian Order; Cistercian monasteries; Stephen Harding; Bernard of Clairvaux; music; reform; Cistercian chant